Reliable Detection of Excessive Sperm Ros Production in Subfertile Patients: How Many Men with Oxidative Stress? - Costanza Calamai; Elena Chelli; Oumaima Ammar; Michele Tanturli; Linda Vignozzi; Monica Muratori (MDPI AG, 2024)
Sperm oxidative stress has been extensively associated to male infertility. However, tests to detect this parameter have not been yet introduced in clinical practice and no definitive data are present on the extent of oxidative stress in male infertility. In this study, we used a novel and reliable flow cytometric method to reveal sperm ROS production in subfertile patients (n = 131) and in healthy donors (n = 31). Oxidative stress was higher in subfertile patients (14.22 [10.21-22.08]%) than in healthy donors (9.75 [8.00-14.90]% (p < 0.01)), but no correlation was found with age, semen quality or sDF. We also failed to detect an increase in sperm ROS production with semen viscosity or leukocytospermia, but a sharp impact of semen bacteria was evident (with bacteria: 31.61 [14.08-46.78]% vs. without bacteria: 14.20 [10.12-22.00]%, p < 0.01). Finally, after establishing a threshold as the 95th percentile in healthy donors, we found that 29% of subfertile patients exceeded this threshold. The percentage decreased to 25.56% when we excluded subjects with bacteriospermia and increased to 60.87% when only these patients were considered. In conclusion, 29% of subfertile patients showed an excessive sperm ROS production. Surprisingly, this parameter appears to be independent from routine semen analysis and even sDF determination, promising to provide additional information on male infertility.